2017
DOI: 10.1097/adm.0000000000000287
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome Comparison Between Telepsychiatry and Face-to-face Buprenorphine Medication-assisted Treatment for Opioid Use Disorder: A 2-Year Retrospective Data Analysis

Abstract: Objectives To retrospectively review clinic records to assess the difference between face-to-face and telepsychiatry buprenorphine Medication-assisted treatment (MAT) programs for the treatment of opioid use disorder on three outcomes: additional substance use, average time to achieve 30 and 90 consecutive days of abstinence, and treatment retention rates at 90 and 365 days. Methods Medical records of patients (N=100) who were participating in telepsychiatry and in face-to-face group-based outpatient bupreno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 15 publications
2
89
2
Order By: Relevance
“…This study reported 51.1% of telepsychiatry patients versus 49.2% of face‐to‐face patients remained in treatment after 90 days. This difference was not statistically significant, although the study's statistical power and generalizability were limited …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This study reported 51.1% of telepsychiatry patients versus 49.2% of face‐to‐face patients remained in treatment after 90 days. This difference was not statistically significant, although the study's statistical power and generalizability were limited …”
Section: Discussionmentioning
confidence: 75%
“…Existing studies demonstrate the use of VTC for diagnosis and assessment of mental health disorders is comparable to face‐to‐face care in a variety of populations across different settings . However, due to financial, legal, and regulatory issues, MAT has not been extensively delivered by telemedicine and there is limited data about its effectiveness when administered this way …”
Section: Introductionmentioning
confidence: 99%
“…Other EDs have implemented similar programs, primarily in areas with high rates of opioid overdose and high population density . Use of on‐call peer support may have limited effectiveness in rural areas; however, there may be a role for telehealth or on‐site peer placement as a means to provide access to peer support notwithstanding large geographic distances …”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has been used for buprenorphine treatment clinically and Weintraub et al (2018) conducted a retrospective chart review of service users and found that this was effective at keeping service users within treatment at 3 months of treatment with 86.1% having opiate negative tests suggesting very good outcomes. Zheng et al (2017) conducted a similar retrospective chart review, comparing outcome measures between telemedicine and face-to-face reviews for buprenorphine treatment. They found that there was no statistically significant difference between additional substance misuse, time to reach 30 to 90 days of consecutive days of abstinence and service user retention rates between 90 and 365 days of treatment between the two groups.…”
Section: Telemedicine In Addictionsmentioning
confidence: 99%